Maintenance management for public building: Ministry of International Trade And-Industry (MITI) / Noor Hidayah Ismail - Ismail, Noor Hidayah (2008)
Recently, public building maintenance in Malaysia is questionable due to numerous maintenance problems and often managed in average level. This study focused on maintenance management for public building in Ministry of International Trade and Industry (MITI). The aims of the study are to identify appropriate approach and strategic planning in implementing maintenance management for public building in MITI. The objective of this study to identify the current practice, the effectiveness and problems occurs in the current maintenance management as well as to indicate the necessary recommendation to improve the current maintenance management system of the public building in MITI. In order to achieve the aims and objectives, literature review was done followed by the details on four case studies which are MITI Office Complex, MATRADE Tower, MlDA and MIDF Tower. Then the data were collected using questionnaires, interview and observation. The collected data was analyzed using Microsoft Excel software. Findings had shown that the current maintenance management for public building in Ministry of International Trade and Industry (MITI) needs improvement due to improper maintenance practice and planning. Most of the respondents highly satisfied with maintenance management applied at MATRADE Tower Complex followed by MIDA Building compared to the MIDF Tower and MITI Office Complex. Therefore, to improve the current maintenance management system for public building, an effective maintenance department and efficient planning on maintenance management essential to optimize the user satisfaction and keeping the building in its best condition.